Genetic diversity, safety and technological characterization of lactic acid bacteria isolated from artisanal Pico cheese. (May 2017) - Domingos-Lopes, M.F.P.; Stanton, C.; Ross, P.R.; Dapkevicius, M.L.E.; Silva, C.C.G.
Abstract: A total of 114 lactic acid bacteria were isolated at one and 21 days of ripening from a traditional raw cow's milk cheese without the addition of starter culture, produced by three artisanal cheese-makers in Azores Island (Pico, Portugal). Identification to species and strain level was accomplished by16S rRNA gene and PFGE analysis. Carbohydrate utilization profiles were obtained with the relevant API kits. Isolates were evaluated according to safety and technological criteria. The most frequently observed genus identified by 16S rRNA sequencing analysis was Enterococcus, whereas API system mostly identified Lactobacillus . The highest percentages of antibiotic resistance were to nalidixic acid (95%), and aminoglycosides (64–87%). All isolates were sensitive to several beta-lactam antibiotics and negative for histamine and DNase production. Gelatinase activity was detected in 49.1% of isolates, 43% were able to degrade casein and 93% were α-hemolytic. Most enterococci presented virulence genes, such as gelE, asaI, ace . Diacetyl production was found to be species dependent and one strain ( Leu. citreum ) produced exopolysaccharides. Selected strains were further studied for technological application and were found to be slow acid producers in milk and experimental cheeses, a desirable trait for adjunct cultures. Two strains were selected on the basis of technological and safety application as adjunct cultures in cheese production and presented the best cheese aroma and flavor in consumer preference tests. This is the first effort to characterize Pico cheese LAB isolates for potential application as adjunct cultures; the results suggest the potential of two strains to improve the quality of this traditional raw milk product. Highlights: LAB microbiota isolated from an Azorean artisanal cheese was investigated. Enterococcus was the dominant genera identified by gene sequence analyses whereas API system mostly identified Lactobacillus. None of isolates showed high-level resistance to clinically important antibiotics. All Enterococcus isolates were sensitive to vancomycin but presented at least one virulence gene. Two Lactobacillus strains were selected for adjuvant cultures in cheese application.